Handover protocol in wireless ATM/ Mohd Lotfi Noor - Noor, Mohd Lotfi (1995)
The Asynchronous Transfer Mode (ATM) is a networking technology for the transport of different types of information, all in fixed sized, small units called cells, and allows this to be done with a predetermined, guaranteed Quality of Service. This paper presents an introduction to the application of Asynchronous Transfer Mode (ATM) in wireless network. The mobility of portable communication devices such as Wireless ATM will affect the signal strength received from the base station. The handover strategies is used to ensure devices transfer to the new base station can maintain the connectivity to the ATM network backbone. The handover protocol is simulated and network performance is evaluated by using a commercial software design tool.